Adolescent self-harm: a school-based study in Northern Ireland. - O'Connor, R; Rasmussen, S; Hawton, K (Elsevier, 2014)
BACKGROUND: The prevalence of adolescent self-harm in Northern Ireland (NI) and its associated factors are unknown. Given the established relationship between conflict and mental health, and NI׳s recent history of conflict, it is important to investigate the factors associated with self-harm in NI. This study aimed to determine the prevalence of self-harm in NI adolescents and the factors associated with it, including exposure to the NI conflict. METHODS: Observational study of 3596 school pupils employing an anonymous self-report survey. Information was obtained on demographic characteristics, lifestyle, life events and problems, exposure to the NI conflict, social and internet influences, and psychological variables. RESULTS: Self-harm was reported by 10% of respondents. In univariate analyses, exposure to the NI conflict was associated with self-harm alongside established risk factors. In multivariate analyses, bullying and exposure to self-harm were associated with lifetime self-harm in both girls and boys. Alcohol use, drug use, physical and sexual abuse, and self-esteem were also associated with self-harm in girls. In boys, absence of exercise, sexual orientation concerns, anxiety and impulsivity were additional risk factors. The internet/social media and the self-harm of others were also key influences. LIMITATIONS: This is a cross-sectional study. CONCLUSIONS: The rate of self-harm was lower than elsewhere in the UK/Ireland. The study highlights the factors which should be considered in terms of risk assessment. In addition to established risk factors, the findings suggest that more research on the legacy of the NI conflict as well as the influence of new technologies warrant urgent attention.